Study of 1-Formyl-2-Pyrazolines as Anticancer Drug Candidates - Artania Adnin Tri Suma; Tutik Dwi Wahyuningsih (Indonesian Journal of Pharmacy, 2023)
The development of novel anticancer agents is essential in cancer prevention. One versatile group of compounds, known for their significant bioactivity and several of its derivatives that have been clinically approved, is the group of pyrazolines. This study aimed to synthesize 1-formyl-2-pyrazoline derivatives (pyrazolines 1-2) using chalcone 1-2, hydrazine hydrate, and formic acid via cyclo-condensation. The synthesized compounds were characterized using Fourier Transform Infrared (FTIR), Gas Chromatography-Mass Spectrometry (GC-MS), and Nuclear Magnetic Resonance (1H- and 13C-NMR) spectrometers. Pyrazolines 1-2 were found to be drug-like compounds, satisfying Lipinski’s Rule of Five and possessing favourable absorption, distribution, metabolism, and excretion (ADME) properties, including good gastrointestinal absorption, blood-brain barrier permeability, and no interaction with P-glycoprotein. Furthermore, they were inactive against several toxicity endpoints in a normal body condition, such as immunotoxicity, mutagenicity, and cytotoxicity. In vitro cytotoxic evaluation of the pyrazolines 1-2 against HeLa and MCF7 cancer cell lines demonstrated moderate activity, with IC50 values of 25.01 µM and 82.87 µM, respectively. Pyrazolines 1-2 also showed good selectivity with selectivity index (SI) values of 8.92 and 14.45. The molecular docking study on epidermal growth factor receptor tyrosine kinase (EGFR-TK) (PDB ID: 4HJO) revealed that pyrazolines 1-2 had a binding affinity of -7.9 and -8.0 kcal/mol, respectively. The compounds interacted with Lys721 residue through hydrogen bonds and hydrophobic interactions due to the presence of the pyrazoline ring and the formyl group in their structures. These findings suggest that pyrazolines 1-2 scaffold has the potential to be further studied as a lead compound for anticancer drug candidates.